Grypsy z Konzentrationslager Auschwitz Józefa Cyrankiewicza i Stanisława Kłodzińskiego - Paczyńska, Irena; Cyrankiewicz, Józef; Kłodziński, Stanisław (Wydawnictwo Uniwersytetu Jagiellońskiego, 2013)
Bibliogr. s. 649-660. Indeks